KENDALA PENERAPAN METODE DISKUSI PADA PEMBELAJARAN BAHASA INDONESIA DI SMP - Fortuna Murdyan Adalea; Markhamah Markhamah (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT The implementation of the discussion method in junior high school Indonesian language learning continues to face challenges that limit students' active participation and the achievement of learning objectives. Problems such as low self-confidence, dominance of a few students, inadequate understanding of learning materials, and ineffective discussion management reduce the effectiveness of classroom discussions. This study aimed to analyze the challenges encountered in implementing the discussion method in Indonesian language learning at the junior high school level and to identify strategies for overcoming these challenges. A descriptive qualitative approach was employed. Data were collected through semi-structured interviews, classroom observations, and documentation involving an Indonesian language teacher and eighth-grade students. The data were analyzed using thematic analysis, while source and technique triangulation were applied to ensure data trustworthiness. The findings revealed five major challenges: students' low self-confidence, poorly managed discussions, dominance by several students, limited understanding of learning materials, and low classroom discipline. Efforts to address these challenges included providing positive reinforcement, supervising and guiding discussions, forming heterogeneous groups, ensuring equal participation opportunities, and strengthening students' understanding through additional explanations, guiding questions, and instructional media. The study concludes that the effectiveness of the discussion method depends on collaboration between teachers and students through well-managed, participatory, and supportive learning environments. ABSTRAK Pembelajaran Bahasa Indonesia di SMP masih menghadapi permasalahan dalam penerapan metode diskusi sehingga keterlibatan aktif siswa dan pencapaian tujuan pembelajaran belum berlangsung secara optimal. Berbagai kendala, seperti rendahnya kepercayaan diri siswa, dominasi beberapa anggota kelompok, kurangnya pemahaman materi, serta pengelolaan diskusi yang belum efektif, menghambat proses pembelajaran. Penelitian ini bertujuan menganalisis kendala dalam penerapan metode diskusi pada pembelajaran Bahasa Indonesia di SMP serta mengidentifikasi upaya yang dapat dilakukan untuk mengatasinya. Penelitian menggunakan metode kualitatif dengan pendekatan deskriptif. Data dikumpulkan melalui wawancara semi terstruktur, observasi, dan dokumentasi terhadap guru Bahasa Indonesia dan siswa kelas VIII. Data dianalisis menggunakan analisis tematik dengan menerapkan triangulasi sumber dan triangulasi teknik untuk menjamin keabsahan data. Hasil penelitian menunjukkan bahwa kendala utama meliputi rendahnya kepercayaan diri siswa, diskusi yang kurang terarah, dominasi beberapa siswa, kurangnya pemahaman materi, dan rendahnya disiplin siswa. Upaya yang dilakukan meliputi pemberian apresiasi, pendampingan dan pengawasan diskusi, pembentukan kelompok heterogen, pemerataan kesempatan berpendapat, serta penguatan pemahaman materi melalui penjelasan ulang, pertanyaan pemantik, dan pemanfaatan media pembelajaran. Penelitian ini menunjukkan bahwa efektivitas metode diskusi memerlukan kolaborasi antara guru dan siswa melalui pengelolaan pembelajaran yang terstruktur, partisipatif, dan kondusif.